A Forgotten Principle in Immunocytochemistry: Optimal Dilution. (November 2022) - Dudás, Bertalan; Lane, Malcolm; Mupparaju, Nikitha; Kim, Hye Min; Merchenthaler, Istvan
Immunocytochemical (ICC) techniques are frequently used in basic and clinical research. Here, we focus on the importance of using antisera/antibodies at optimal dilutions to achieve specificity and reduce costs. Unfortunately, the basic principle, the necessity to test method specificity of the staining by a series of increasing dilutions of primary antiserum/antibodies, is only occasionally seen in papers using ICC. Many researchers rely on the company's information or others' published data. In this study, we show examples with monoclonal antibodies used in the peroxidase-based ICC technique in mouse and guinea pig brain sections. We show images of ICC staining of phospho-S129 alpha-synuclein in A53T mice and NeuN in guinea pig brains and demonstrate that optimal staining with them can be achieved at least at two to three orders of magnitude higher dilutions than generally used in the literature. We strongly recommend that when antisera/antibodies are used for the first time in any laboratory, independent of what the manufacturer or vendor recommends or are found in the literature, a dilution curve should be set up to identify the optimal dilution. This practice provides not only the highest specificity but is also an economic approach.